2018
DOI: 10.1123/pes.2017-0112
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory Responses During Submaximal Exercise in Children With Prader–Willi Syndrome

Abstract: PWS did not show impaired ventilatory responses to exercise. Hyperventilation in PWS may relate to excessive neural stimulation and metabolic cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Adults with PWS showed lower values of maximal oxygen uptake (~47%) and ventilatory threshold (~44%) than overweight and obese adults without PWS . A worse exercise efficiency during low‐to‐moderate aerobic exercise (ie, higher oxygen uptake or higher ventilation rate for a given muscle power output) was also reported in children with PWS compared to normal‐weight children without PWS …”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Adults with PWS showed lower values of maximal oxygen uptake (~47%) and ventilatory threshold (~44%) than overweight and obese adults without PWS . A worse exercise efficiency during low‐to‐moderate aerobic exercise (ie, higher oxygen uptake or higher ventilation rate for a given muscle power output) was also reported in children with PWS compared to normal‐weight children without PWS …”
Section: Resultsmentioning
confidence: 89%
“…A consistently higher HR during submaximal exercise (12%-14%) at the same absolute workload was also reported in children with PWS compared to normal-weight or obese children. 25 With regard to blood pressure (BP), similar levels of systolic BP were found in children with or without PWS. 16,22,33 However, one study observed a higher post-exercise diastolic BP in children with PWS compared to lean and obese children without this condition (24% and 11% lower, respectively).…”
Section: Acute Response To Exercisementioning
confidence: 88%
See 3 more Smart Citations